Evaluating Communication through Work Authorization between Dentists and Dental Technicians for Fixed Prosthesis : Communication in Fixed Prosthesis Work Authorization - Bashir, Anam Fayyaz; Jatala, Ussamah Waheed; Ahmad, Moeen ud Din; Butt, Aisha Arshad; Qaiser, Aneela; Munir, Nadia (Pakistan Journal of Health Sciences, 2024)
Communication within the dental profession can be challenging and may affect the quality of prostheses delivered to the patient. A methodical investigation into the dynamics between dentists and dental technicians is lacking in Lahore. Objective: To assess adequate practice of communication between dentists and dental technicians through work authorization for fixed prosthesis. Methods: This cross-sectional study was conducted in dental laboratories of Lahore. A questionnaire concerning work authorization forms was distributed to 80 dental technicians through Google Forms and hard copies. The survey concentrated on inquiries related to various aspects of work authorization, including gender, years of experience, impression disinfection, patient demographic data, impression materials used, fixed prosthesis design, and shade selection. An adequate work authorization was assessed in the end. Statistical analysis was conducted SPSS version 25.0 and was analyzed using chi-square, with significance set at p ≤ 0.05. Results: Out of the 80 survey forms disbursed, only 73 completely filled responses were accepted, giving a response rate of 91%. Information regarding patient demographic data (19.2%), patient photographic record (5.5%), pontic design (13.7%), margin design (37%), surfaces covered by metal (9.6%) and occlusal scheme (6.8%), were all on the inferior side of the scale ranging below 40%. Adequate practice of work authorization was discouraging, at only 17.8%. Conclusions: Poorly filled work authorization forms lead to patient and dentist dissatisfaction with fixed dental prostheses. This highlights the importance of clear communication between technicians and dentists. Dental students should learn to complete these forms during their training.